Between Texts and Contexts: Contemporary Muslim Gender Roles. Issue 3 (2nd July 2016) - Samani, Shamim
ABSTRACT: Based on research conducted in Western Australia as part of a PhD thesis, this article looks at the shifting boundaries of gender roles in Australian Muslim households. It highlights the Islamic stance on the biological differences between men and women as the basis for understanding gender roles and responsibilities. It also uncovers how the ideal influences contemporary Muslim gender roles and the interplay of social and economic factors that impact upon Australian Muslim households in their acculturation in the more liberal Western setting. In order to capture the nuances of perceptions and accounts of how the participants in the research perceive providing and caring roles in the household unit, the primary research uses narrative enquiry as part of its methodology. The findings show that there is variance between the textual injunctions and contextual realties as Muslim women also become providers for the household. While this shows that there is congruence with the mainstream Australian society, it also has implications for how gender equality and economic empowerment of women are approached in a diverse society like Australia.